The Effectiveness of Intensive Short Term Dynamic Psychotherapy on Clinical Symptoms and Academic Performance in Adolescents with Oppositional Defiant Disorders - Mahnaz NikAkhlagh Abbasi; Davood Manavipour (Iranian Evolutionary Educational Psychology Journal, 2023)
Oppositional defiant disorder (ODD) can have negative consequences in personal, social, family, and academic dimensions. Thus, it is crucial to find appropriate solutions to improve symptoms and reduce the consequences of this disorder. This study aimed to examine the effect of short-term intensive psychotherapy on clinical symptoms and academic performance in adolescents with ODD using a quasi-experimental pretest-posttest design with a control group. The statistical population included all ODD adolescents in high schools within district 4 of Tehran, from which 30 individuals were purposefully selected and randomly assigned to the experimental and control groups. Short-term intensive psychotherapy was administered to the experimental group, while the control group received no intervention. Data were collected using the Oppositional Defiant Disorder Rating Scale (ODDRS) and the Student Academic Performance Questionnaire (SAPQ), and one way analysis of covariance was used to analyze the data in SPSS-19. The results showed that short-term intensive psychotherapy was effective in improving clinical symptoms and academic performance in adolescents with ODD (p<0.05). Therefore, it can be concluded that short-term intensive psychotherapy can improve clinical symptoms and academic performance in male adolescents with ODD. To empower and improve the mental health of individuals with ODD, it is recommended to conduct an educational program based on this treatment in counseling and psychotherapy centers.